2005
DOI: 10.1021/la0515221
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Micrometer-Scale Adhesion by Tuning Nanometer-Scale Surface Features

Abstract: This article demonstrates how the adhesion rates of micrometer-scale particles on a planar surface can be manipulated by nanometer-scale features on the latter. Here, approximately 500-nm-diameter spherical silica particles carrying a substantial and relatively uniform negative charge experienced competing attractions and repulsions as they approached and attempted to adhere to a negative planar silica surface carrying flat 11-nm-diameter patches of concentrated positive charge. The average spacing of these pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
135
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(147 citation statements)
references
References 86 publications
12
135
0
Order By: Relevance
“…As can be seen, there was significant deposition of particles even in the case when the averaged zeta potential of the surface was of the same sign as the particle zeta potential. Similar observations were done in case of PAH covered mica [40] and the deposition of silica particles onto quartz sand modified to various degrees by the silanization procedure [39]. These observations contradict theoretical predictions stemming from the classical DLVO theory depicted by the dashed line in Fig.…”
Section: Comparison With Experimental Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…As can be seen, there was significant deposition of particles even in the case when the averaged zeta potential of the surface was of the same sign as the particle zeta potential. Similar observations were done in case of PAH covered mica [40] and the deposition of silica particles onto quartz sand modified to various degrees by the silanization procedure [39]. These observations contradict theoretical predictions stemming from the classical DLVO theory depicted by the dashed line in Fig.…”
Section: Comparison With Experimental Resultssupporting
confidence: 67%
“…15 seems quite universal, because it has also been observed in other polyelectrolyte/substrate systems, for example, for the PAH/mica system [40] or pDMAEMA/ silica system [39]. Because of similarities in chemical composition, it can be expected that analogous particle adsorption mechanism will appear in the case of surfaces covered by proteinous layers.…”
Section: Comparison With Experimental Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…[10][11][12] The typical size of organosilica particles synthesized using Stöber conditions is often greater than 500 nm. 6,7,9 The Stöber method was also used to generate mesoporous materials, where homo-or co-condensation of TEOS with other functional silanes was conducted in the presence of low molecular weight or polymeric surfactants as a template. 1,10,13 Fewer studies have reported the development of organosilica nanoparticles with sizes smaller than 200 nm.…”
Section: Introductionmentioning
confidence: 99%